Construction of Artificial Vagina - Banerjee, M. S. (Indian Journal of Plastic Surgery, 1973)
1. The present series consists of 11 cases of congenital absence of vagina. Surgical construction of artificial vagina was done in 10 cases following Shears' modification of Wharton's technique.2. Initially, split thickness skin graft was used only in I case. Of the remaining 9, only 6 had spontanous epithelisation of the cavity, 2 subsequently required insertion of skin graft, and I had contracture of vagina.3. Importance of skin grafting of the newly constructed canal is emphasized.4, Long term result was satisfactory in all married women.